PENGARUH CELEBRITY ENDORSEMENT DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SKINTIFIC PADA TOKO UNDERPRICE SKINCARE - Agnelisa Fegyola Pinem; Finta Aramita; Muhammad Yamin Siregar (SUAN PUBLISHER, 2024)
The aim of this research is to determine the influence of celebrity endorsements and brand awareness on purchasing decisions for Skintific skincare products at Underprice Skincare stores, partially and simultaneously. The research design used is an associative approach. The population of the population who purchased skintific products at Underprice Skincare was 2,321 consumers (Data on purchases at Underprice Skincare stores in 2022 using a sampling technique based on criteria using the Slovin method. Based on these criteria, the research sample was 96 respondents. The data analysis method used analysis multiple linear regression with SPSS.25 Based on the results of the t test that has been carried out, it can be concluded that Celebrity Endorsement has a positive and significant effect on Purchasing Decisions. It can be concluded that Brand Awareness has a positive and significant effect on Purchasing Decisions Endorsement and Brand Awareness have a positive and significant effect simultaneously on purchasing decisions